Health problems of professional ballet dancers: an analysis of 1627 weekly self-reports on injuries, illnesses and mental health problems during one season - Junge, A.; Hauschild, A.; Stubbe, J. H.; van Rijn, R. M. (Sports Medicine - Open, 2024)
Background Several studies have investigated injuries of (pre-)professional ballet dancers, however most used a medical-attention and/or time-loss defnition and did not analyse the prevalence of all health problems. The aim was to analyse the frequency and characteristics of all self-reported physical and mental health complaints (i.e. inju ries, illnesses and mental health problems) of professional ballet dancers during one season.